ANALISA PEMBEBANAN DAN DAYA DUKUNG TANAH DENGAN PONDASI TIANG PANCANG BERDASARKAN DATA N-SPT PADA PEMBANGUNAN GEDUNG IAIN PADANGSIDEMPUAN - Marudut Tua Debataraja, Semangat; Nandawijaya Zebua, Abid; Fitra, Joni (Jurnal Sains dan Teknologi ISTP, 2024)
Foundations are a type of construction that forms the basis of a building in direct contact with the ground and functions as a support for the building above it, aiming to transfer vertical and horizontal loads gradually and evenly to the soil layers. The IAIN Padangsidempuan North Sumatra Building project will begin construction from January 6 2022 to October 30, 2022. This building is intended for lecture halls with a capacity of 5 floors. Using a pile foundation with a depth of 18 meters with a diameter of 0.5 meters. From the calculation results, it is found that the carrying capacity of 1 pile for PC4D50 = 154.92 tons and the bearing capacity of the foundation in the group is Qg PC4D50 = 406,509 tons and PC3D50 = 154.92 tons, and in 1 group PC3D50 = 349,963 tons, which is different from the initial plan for 1 pole. for PC4D50 it is = 157.84 tons and for 1 group = 414.17 tons and for PC3D50 for 1 pole = 157.84 tons and for 1 group = 356,561 tons. For PC4D50 the results are as follows: For Direction D19 – 150, for PC3D50 obtained as follows: For Direction Initial planning Y direction D19 – 150.